2014
DOI: 10.1155/2014/968262
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of HLA-DQB1 Contribution to Susceptibility of Dengue Serotype 3 in Dengue Patients in Southern Brazil

Abstract: Dengue infection (DI) transmitted by arthropod vectors is the viral disease with the highest incidence throughout the world, an estimated 300 million cases per year. In addition to environmental factors, genetic factors may also influence the manifestation of the disease; as even in endemic areas, only a small proportion of people develop the most serious form. Immune-response gene polymorphisms may be associated with the development of cases of DI. The aim of this study was to determine allele frequencies in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…For HLA class I MHC restricted responses, it has been recently shown that different allelic variants are associated with differential magnitude of anti-DENV responses and that HLA alleles known to be associated with increased risk of severe DENV disease are associated with weaker CD8 + T-cell responses (18). Similarly, certain MHC class II alleles have been described as associated with increased protection from severe disease (9,15,(19)(20)(21). Thus, T-cell responses are likely to contribute to protection from dengue disease.…”
mentioning
confidence: 99%
“…For HLA class I MHC restricted responses, it has been recently shown that different allelic variants are associated with differential magnitude of anti-DENV responses and that HLA alleles known to be associated with increased risk of severe DENV disease are associated with weaker CD8 + T-cell responses (18). Similarly, certain MHC class II alleles have been described as associated with increased protection from severe disease (9,15,(19)(20)(21). Thus, T-cell responses are likely to contribute to protection from dengue disease.…”
mentioning
confidence: 99%
“…2B). The genes found by scPCA include CD38, HLA-DQB1, and RSAD2 (Viperin), which have been previously associated to the susceptibility to, protection against, or presence of dengue [5,4,6]. For a full list of these genes, refer to Table S1 and Table S2.…”
Section: Dengue Microarray Datamentioning
confidence: 99%
“…Dengue merupakan virus RNA beruntai tunggal yang termasuk dalam genus Flavivirus dengan nama famili Flaviviridae. [2][3][4] Transmisi DENV antar manusia diperantarai oleh vektor nyamuk spesies Aedes aegypti dan Aedes albopictus. Gejala infeksi mulai terlihat dalam rentang 4-7 hari setelah gigitan nyamuk dan bertahan selama 3-10 hari.…”
unclassified